Conference Scene: Cell and gene therapies: clinical and near-clinical focus. (May 2011) - Haley, N Rebecca
The Phacilitate Cell and Gene Therapy Forum was a showcase of the steps required for translational medicine. The major focus was on requirements from early phase discovery through to the regulatory and business processes to bring treatments to patients. Talks on discovery and new methodologies and technologies were presented in light of adaptability to treatment regimens. Venture capitalists and bank representatives, external evaluators of these new treatments, gave valuable financial process insight. US FDA officials offered explanation and advice on successful approaches to the regulatory challenges to this new and emerging field. Completing the picture were talks from contract suppliers and manufacturers of necessary materials and equipment.